Madrasah Chief Leadership in Human Resource Development in Madrasah Ibtidaiyah Muhammadiyah 2 Kedungbanteng - Ahmad Bukron; Renny Oktavia; Akhtim Wahyuni (International Consortium of Education and Culture Research Studies, 2020)
Leadership or often called leadership according to the literal meaning is days lead or the quality of the leader. The leadership is an activity or art to influence the behavior of people who are led to be willing to work together towards one goal that is set or desired together. While the development of human resources is an effort to develop existing in an educational institution. The focus of this research is to explore the leadership pattern of a madrasah head in order to develop human resources, in this case educators and educational staff. This research uses a descriptive method carried out through data collection in the field giving an overview of madrasah head leadership, this research approach uses qualitative approach This research data in the form of quotes, words, phrases, and story sentences. Data sources in this study were observations of Madrasah Ibtidaiyah Muhammadiyah 2 Kedungbanteng Tanggulangin.